NURSING CARE OF NEONATAL JAUNDICE IN HYPERBILIRUBINEMIA BABIES: A CASE REPORT - Tyas, Anestasia Pangestu Mei; Nurvianti, Siti Aisyah; Mardhika, Amellia; Medawati, Riris; Lutfiandini, Cherlys Tin; Lestari, Wahyu Agustin Eka (Universitas Airlangga, 2021)
Introduction: Jaundice is a condition that is often found in the 24 hours after the birth of the baby due to hyperbilirubinemia. Hyperbilirubinemia can cause various complications and death if not treated properly and immediately. The knowledge and ability of nurses in providing nursing care for neonatal jaundice still need to be improved. This study aims to describe nursing care for neonatal jaundice in hyperbilirubinemia infants. Methods: This study uses a case study approach design through the nursing process with a sample of a hyperbilirubinemia baby with neonatal jaundice nursing problems. Data collection techniques were carried out through interviews, observations, physical examinations and documentation studies. Data analysis in this study uses narrative analysis. Results: The case report found jaundice on the skin, sclera, and mucosa. The nursing diagnosis in this study was neonatal jaundice associated with less than 7 days of age. The intervention provided in the form of phototherapy and breastfeeding education showed the result was not found jaundice on the skin, sclera, and mucosa after three days. Conclusion: The provision of phototherapy and breastfeeding education is effective in solving neonatal jaundice.